2007
DOI: 10.1051/0004-6361:20077257
|View full text |Cite
|
Sign up to set email alerts
|

Flaming, bright galaxies along the filaments of A 2744

Abstract: Context. The existence of a lumpy, large-scale filamentary structure is at the basis of the current paradigm of cosmic formation and evolution of clusters. The star-formation history of galaxies falling into a cluster is altered as a result of the environmental stresses. Aims. We investigate the relation between substructure and properties of the galaxy population in a 30 × 30 region centred on the massive merging cluster A 2744 at z ∼ 0.3. Methods. Multi-object spectroscopy at low resolution and BVR photometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 44 publications
10
56
0
Order By: Relevance
“…4. A filament is a low density environment and as such is dominated by blue late-type galaxies (Braglia et al 2007). We found that 12 of the 14 galaxies inside r 200 brighter than L * are on the cluster red-sequence.…”
Section: Discussionmentioning
confidence: 99%
“…4. A filament is a low density environment and as such is dominated by blue late-type galaxies (Braglia et al 2007). We found that 12 of the 14 galaxies inside r 200 brighter than L * are on the cluster red-sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Red galaxies with low levels of ongoing star formation are assumed to be the descendants of blue star-forming galaxies that have been accreted from the surrounding filamentary structure and quenched by specific processes operating within the cluster environment (e.g. Braglia et al 2007;Verdugo et al 2012). How spirals were transformed into ellipticals remains unclear (e.g.…”
Section: Blue-galaxy Fractionmentioning
confidence: 99%
“…The precise lensing mass distribution has been determined by utilizing the deepest HST data from the Frontier Fields program Wang et al 2015). Large-scale galaxy filaments in the south and northwest directions were first noted by Braglia et al (2007). Spectroscopically identified 343 member galaxies within 3 Mpc from the cluster center were catalogued by Owers et al (2011), with which a galaxy concentration in the east-northeast was also recognized.…”
Section: Introductionmentioning
confidence: 99%